Recent contributions from solid-state NMR to the understanding of membrane protein structure and function - Judge, P; Watts, A (2011)
The plasma membrane functions as a semi-permeable barrier, defining the interior (or cytoplasm) of an individual cell. This highly dynamic and complex macromolecular assembly comprises predominantly lipids and proteins held together by entropic forces and provide the interface through which a cell interacts with its immediate environment. The extended sheet-like bilayer structure formed by the phospholipids is a highly adaptable platform whose structure and composition may be tuned to provide specialised functionality. Although a number of biophysical techniques including X-ray crystallography have been used to determine membrane protein structures, these methods are unable to replicate and accommodate the complexity and diversity of natural membranes. Solid state NMR (ssNMR) is a versatile method for structural biology and can be used to provide new insights into the structures of membrane components and their mutual interactions. The extensive variety of sample forms amenable for study by ssNMR, allows data to be collected from proteins in conditions that more faithfully resemble those of native environment, and therefore is much closer to a functional state. © 2011.